NUMERICAL MODELING OF COASTAL TIDES AND CURRENT PATTERN AT NORTHERN PEAT COAST OF BENGKALIS ISLAND - Daly Riandi; Sigit Sutikno; Muhamad Yusa (LPPM Universitas Abdurrab, 2024)
Riau Province experiences a loss of coastline every year due to erosion. The northern coast of Bengkalis Island is prone to coastal setback. Apart from land collapse, erosion is also caused by the flow of water along the coast. To be able to carry out good disaster management, accurate coastal hydrodynamic modelling is important. Some important components of hydrodynamics are tidal characteristics and current patterns. These important components are identified using numerical models. Manning parameter calibration is used to improve the model's accuracy. The tidal characteristic obtained was mixed, predominantly semidiurnal. Meanwhile, the pattern of tidal currents is known from the direction of movement. At spring tide, water moves towards the south and southwest with an average speed of 0.210 m/s and at neap tide, it moves towards the northeast with an average speed of -0.232 m/s.